Exploring the social innovation research field based on a comprehensive bibliometric analysis - Agnieszka Janik; Adam Ryszko; Marek Szafraniec (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Due to the growing academic interest in social innovation, there is a need for a comprehensive bibliometric analysis of the structure and evolution of this research field. So far, there have been very few in-depth studies in this area. In addition, the number of publications in this domain grows dynamically year by year. For this reason, it was assumed that the existing research needs expansion and updating. Therefore, this study presents a comprehensive bibliometric analysis aiming to identify research patterns and trends in the scientific literature on social innovation. Descriptive and performance analyses as well as research field mapping based on network analyses were performed. The most productive authors, sources, academic organizations, and countries in the social innovation literature were indicated. Moreover, the most influential authors and publications in the analyzed research field were determined. Furthermore, the evolution of social innovation research and the scientific collaboration in this area were shown and characterized. The analysis results were intended to show academics and practitioners an up-to-date, comprehensive picture of the multidisciplinary and multifaceted phenomenon of the research on social innovation.
Keywords: 650; network analysis; social innovation; bibliometric analysis; descriptive and performance analysis; research field mapping